1997
DOI: 10.1111/j.1398-9995.1997.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of asthma in adults – report from the Obstructive Lung Disease in Northern Sweden Study

Abstract: Incidence studies offer a better opportunity to study risk factors for asthma than do prevalence studies. However, regular prospective follow-ups of large cohorts are difficult to perform, and that is why direct measurement of the incidence rate of asthma is almost impossible. Thus, cross-sectional follow-up studies of defined cohorts can be used to provide data on incidence. In 1986, a postal questionnaire survey on respiratory symptoms and diseases was performed in the northernmost province of Sweden. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
99
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 29 publications
(38 reference statements)
10
99
1
2
Order By: Relevance
“…However, some recent longitudinal studies have reported different rates. RÖ NMARK et al [4] from Sweden found an incidence rate of 5 cases?1,000 person-yrs -1 among adults; the high incidence may be caused by the higher ages in the sample, 42-73 yrs. In one Canadian study [17], a remarkably high incidence was found, y6 cases?1,000 person-yrs -1 among males and 12 cases?1,000 person-yrs -1 among females, all 25-54 yrs of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some recent longitudinal studies have reported different rates. RÖ NMARK et al [4] from Sweden found an incidence rate of 5 cases?1,000 person-yrs -1 among adults; the high incidence may be caused by the higher ages in the sample, 42-73 yrs. In one Canadian study [17], a remarkably high incidence was found, y6 cases?1,000 person-yrs -1 among males and 12 cases?1,000 person-yrs -1 among females, all 25-54 yrs of age.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic criteria for new-onset asthma have been based on either clinical investigations, or self-reported asthma or physician-diagnosed asthma [1,2]. Reports on asthma are more common and, over the last 10 yrs, questionnaire-based incidence studies have been published in the USA, Scandinavia, Spain and Italy, showing incidence rates from 1-5 cases per 1,000 person-yrs -1 [3][4][5][6][7][8][9]. It is difficult to decide which subjects should be excluded from the baseline population in a prospective study of asthma incidence.…”
mentioning
confidence: 99%
“…The prevalence of asthma and allergic disease has in-401 creased in many countries [39,40] and there has been spec- asthma and allergies in U.S. children [24].…”
mentioning
confidence: 99%
“…Th2 cells secreting IL-4, IL-5, and IL-13 play a 39 central role in initiating and sustaining the asthmatic response 40 in this model [8]. While Th2 cells promote airway inflamma-41 tion in asthma, it has been proposed that Th1 cells protect 42 against allergic disease by antagonizing Th2 activity.…”
mentioning
confidence: 99%
“…La presencia de síntomas respiratorios también se encontró asociada a otros factores descritos en la literatura científica, como factores de riesgo para la presencia de enfermedad respiratoria en la población adulta mayor, como son la edad, el sexo (29,30), el consumo de cigarrillo (31,32), la humedad en la vivienda (33)(34)(35)(36), la condición socioeconómica (37)(38)(39)(40), la afiliación a la seguridad social, la presencia de enfermedades concomitantes y otras fuentes de contaminación atmosférica como la ocupacional (41,42) y la cercanía a cultivos de caña de azúcar, que son quemados para su cosecha (43).…”
Section: Discussionunclassified